Development of energy conversion for hydrokinetic and wind energy for portable energy harnessing devices - Muhamad Syamim, Muhamad Rosdi (2022)
This project emphasizing hybrid energy harnessing device which covers hydrokinetic and wind energy. The use of hybrid turbine system can be implemented in both condition to generate electricity as an alternative. This project focusing on the portability of the device to be mobile and easy to configure. Hence, several keys are being highlighted in term of size and possible energy extraction for the proposed device. Also, the characteristic of wind speed and fluctuation of water velocity are the challenges to be consider. This thesis will explain about the design of horizontal Savonius turbine with four (4) blade and device casing as well as the raw energy harnessed via DC generator to develop a hybrid hydrokinetic and wind energy for portable energy harnessing device. The development of the device implement the usage of TinkerCAD software for designing and fabricated thoroughly through assembly process while several value-added process were included along the way. The results shows that the effects of velocity on voltage generated and the effects of load on DC generator.